The Effect of Ginger Compresses on Dysmenorrhea in Young Women in The Semanggi Village Surakarta - Shinta, Fitri Nur; Susilowati, Tri (Jurnal Kesehatan Komunitas Indonesia, 2023)
Background: Most of teenage girls who are menstruating experience several symptoms and the largest number of these symptoms is heartburn or menstrual pain (dysmenorrhea). One of the therapies that can be done for women who experience dysmenorrhea is ginger compresses. The general content in ginger can also provide a warm effect and cause enlargement of the veins which will increase blood circulation to the cell membrane so that the uterine muscles relax. Objective: To determine the effect of ginger compresses on dysmenorrhea in young womens in Semanggi Village. Methods: Quantitative research with quasi experiment design using one group pre-test – post-test design, non-probability sampling technique, using purposive sampling method with a sample of 43 respondents, research instrument through NRS (Numeric Rating Scale) questionnaire. Results: After analyzing the data using the wilcoxon test, the p-value (0.000)<0.05 was obtained. Conclusion: There is an effect of ginger compresses on dysmenorrhea in young women in the Semanggi Village, Surakarta.